Correlation between Running Distance and Iliotibial Band Syndrome among Yogyakarta Runners - Konara Budi Sudrajat; Farid Rahman (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Running is a sport with the largest number of participants worldwide. This sport is one of the most frequently held sports. Iliotibial band syndrome (ITBS) is a common syndrome in runners. It even becomes the second most common injury occurring in 1.6% - 12% of all injuries in runners. ITBS can affect up to 10% of active runners. Excessive tension in the iliotibial band (ITB) causes infection and tissue compression, causing iliotibial band syndrome (ITBS). This research aimed to understand the relationship between running distance and the incidence of iliotibial band syndrome in runners. This study used a correlation study method with a cross-sectional approach. In this study, the authors applied the non-probability and incidental sampling techniques. The samples of the study were 80 runners who had consistently run for more than three months. The research data collection instruments included Ober's test for iliotibial band syndrome and a Google form questionnaire for the respondent history. Hypothesis testing used the Chi-Square. The data analysis on the relationship between running distance and the incidence of iliotibial band syndrome found no relationship. It indicates that running distance does not affect the incidence of iliotibial band syndrome in runners. The authors hope that this research can become a baseline or basis for developing preventive interventions for iliotibial band syndrome.